OVERVIEW OF BLOOD PRESSURE AND BLOOD SUGAR LEVELS INELDERLY PEOPLE AT THE SINDUADI VILLAGE - Utami Utami; dede efendy (International Journal of Nursing and Midwifery Science (IJNMS), 2025)
This study aims to describe the status of blood pressure and blood sugar levelsamong elderly people at the Sinduadi Health Center. A descriptive quantitativemethod with a cross-sectional design was used, involving 97 elderlyrespondents selected through total sampling. Data collection included directmeasurement of systolic and diastolic blood pressure as well as random bloodglucose levels. The results showed that the average age of respondents was67.36 ± 6.55 years, with an average systolic blood pressure of 133.63 ± 16.66mmHg and diastolic blood pressure of 75.12 ± 11.50 mmHg. The mean bloodglucose level was 140.03 ± 70.83 mg/dL. Most respondents were classified aspre-hypertensive (49.5%), followed by hypertensive (30.9%) and normal(19.6%), while for blood glucose, 62.9% were normal, 22.7% pre-diabetic,and 14.4% diabetic. The findings indicate that elderly people at the SinduadiHealth Center tend to experience increased blood pressure and blood glucoselevels with age. This pattern emphasizes the importance of routine monitoringof blood pressure and blood sugar levels and the implementation of healtheducation programs for lifestyle modification to prevent the progression ofnon-communicable diseases such as hypertension and diabetes mellitusamong the elderly population.